Effects of two organomodified clays intended to food contact materials on the genomic instability and gene expression of hepatoma cells. (February 2016) - Maisanaba, Sara; Jordá-Beneyto, María; Cameán, Ana M.; Jos, Ángeles
Abstract: Globally, food industries have made significant progress in order to increase the shelf-life of food products and have fewer economic losses. In this sense, the use of organomodified clays destined to be incorporated in polymer matrices play a novel role, leading to improved materials named nanocomposites with enhanced technological profiles. Due to the presence of these clays into the package, the safety of the consumers is a main concern. Cloisite ® 30B and Clay1 are two organomodified clays containing quaternary ammonium salts as modifiers, that can be potentially used to reinforce packaging polymers. Available toxicity data about these clays, specifically genotoxicity, is still limited and inconclusive in some aspects. Thus, the purpose of this work was to evaluate both clays ability to induce genomic instability through the cytokinesis block micronucleus cytome assay (CBMN) and for the first time, their influence in the modulation of several genes involved in genotoxicity and cell death mechanisms. Overall, no genotoxicity response was obtained in any case at the conditions tested. On the other hand, significant expression changes were observed on the genes selected. Nevertheless, further studies are highly needed to elucidate and increase the knowledge about the molecular mechanisms of clays toxicity. Graphical abstract: Highlights: Cloisite ® 30B and Clay1 are new organomodified clays intended to food packaging. Cloisite ® 30B do not induce genotoxicity in HepG2 cells. Clay1 induces only significant differences in Buds, but not in other parameters. Cloisite ® 30B and Clay1 changed significantly the expression of selected genes.